Iron deficiency in endure athletes - Michał Rogulski; Yauheniya Patarocha; Aleksandra Ślusarska; Jolanta Mędyk; Paulina Błasiak; Małgorzata Wirkijowska; Patryk Mikołajec; Ruslan Huk; Barbara Bilecka; Jakub Wirkijowski (Quality in Sport)
Iron deficiency, with or without anemia, is more prevalent in endurance athletes than in the general population. Especially in marathon and half-marathon runners - these groups of endurance athletes are at high risk for iron deficiency via several mechanisms, such as sweating, gastrointestinal bleeding, urinary-tract blood loss, hemolysis, and others.